2007
DOI: 10.1093/eurheartj/ehl504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypertension on anticoagulated patients with atrial fibrillation

Abstract: Hypertension contributes to increased stroke and SEE in AF. Event rates markedly increase at SBP levels of > or = 140 mmHg. The higher stroke rates observed in SPORTIF III compared with SPORTIF V may be related to the greater proportion of subjects with SBP > or = 140 mmHg during the trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
81
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(88 citation statements)
references
References 15 publications
3
81
1
3
Order By: Relevance
“…20,21 Although no relationship between the risk of bleeding and the quartiles of systolic blood pressure was observed in the SPOR-TIF cohort, the impact of blood pressure control on the risk of ischaemic stroke and bleeding events were not investigated. 19 In this study, the incidences of ischaemic stroke in hypertensive and normotensive patients were comparable when the INR control was similar between the two groups. These findings suggest that thromboembolism is related to AF rather than hypertension per se is a more important determinant of ischaemic stroke in our patient cohort with AF.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…20,21 Although no relationship between the risk of bleeding and the quartiles of systolic blood pressure was observed in the SPOR-TIF cohort, the impact of blood pressure control on the risk of ischaemic stroke and bleeding events were not investigated. 19 In this study, the incidences of ischaemic stroke in hypertensive and normotensive patients were comparable when the INR control was similar between the two groups. These findings suggest that thromboembolism is related to AF rather than hypertension per se is a more important determinant of ischaemic stroke in our patient cohort with AF.…”
Section: Discussionmentioning
confidence: 51%
“…5,6 A recent analysis from the Stroke Prevention using an ORal Thrombin Inhibitor in atrial Fibrillation Trial (SPORTIF) has shown that the risk of the systemic thromboembolism and stroke in patients with non-valvular AF increased with the level of systolic blood pressure. 19 It is possible that poorly controlled blood pressure might contribute an increased risk of ischaemic stroke and bleeding, especially intracranial bleeding in patients with non-valvular AF. 20,21 Although no relationship between the risk of bleeding and the quartiles of systolic blood pressure was observed in the SPOR-TIF cohort, the impact of blood pressure control on the risk of ischaemic stroke and bleeding events were not investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, analysis from the Stroke Prevention using an ORal Thrombin Inhibitor in Atrial Fibrillation Trial (SPORTIF) has demonstrated that level of systolic BP correlated with the risk of the systemic thromboembolism and stroke in patients with non-valvular AF. 68 Recent retrospective analysis also showed that hypertensive patients who achieved target BP control (o130/80 mm Hg) had a lower ischemic stroke (0.9% versus 3.1% per year, P ¼ 0.01), but similar bleeding risk compared with those not achieving target BP. 69 These studies highlighted the importance of achieving optimal BP control in hypertensive patients with AF to maximize the benefit of OAC therapy for stroke prevention.…”
Section: Anticoagulation Therapymentioning
confidence: 97%
“…2 There is suggestive evidence that the risk-adjusted incidence of cardioembolic ischemic stroke in patients with atrial fibrillation has declined over the past 2 decades, perhaps in response to more aggressive treatment of underlying risk factors such as hypertension and hyperlipidemia. [3][4][5] As a result, the balance between the risk and benefit of anticoagulation therapy in patients with non-valvular atrial fibrillation may be shifting. These two trends, the increasing incidence of warfarin-associated ICH and the decreasing risk of cardioembolic ischemic stroke in patients with AF, underscore the imperative to develop better tools to predict the risk of warfarin-associated ICH to improve "personalized" decision-making about anticoagulant therapy for patients with AF.…”
mentioning
confidence: 99%